La construcción narrativa de Lactancio: una aproximación a la intención historiográfica en De mortibus persecutorum (s. IV d.C.) - Pablo Castro Hernández (Talia dixit, 2017)
In this paper we analyze the narrative and methodological construction of the work De mortibus persecutorum, written by Lactantius in the fourth century AD. First, we examine the narrative characteristics that define both the apologetic and the historiographical genre. Subsequently, we review these narrative features in the work of Lactantius, demonstrating that his writing has a historiographical intention in order to transmit a historical memory of Christianity in the Roman world.